Designing Boardgame Media for Child Growth Stimulation Through Children’s Games - Nurlailis Saadah; Budi Joko Santosa; Budi Yulianto; Uswatun Khasanah (Journal of Global Pharma Technology, 2020)
Introduction: Educating children requires interesting and safe media. Childhood is a period of growth and development of various aspects which include fine motor, gross motoric, language, and social personal. Social interaction can use technology that is not limited to space and time through gadgets. If there is no control over the use of gadgets, children can become addicted to them, indifferent to those around them, and rarely communicate with people around them. To anticipate this, alternative media that are safer than gadgets is game board. Methods: This research method included 2 phases. Phase I was Research & Development model research, Phase II was the implementation of the model using Pre-Experimental Design research that applies non-randomized One-Shot Case Study. Data were collected by using interview, questionnaire and observation. The data was processed using the visual comparison matrix analysis method. An attractive game board must be supported by a good mechanism and visibility. Results: Children can grow and develop well if a healthy lifestyle is implanted like healthy food is. The solution to this problem can be achieved by designing educational board games as a medium for learning and playing. The reason is that board games have rules, goals, problems, players, procedures, etc. It can also train psychomotor, emotional, moral, cognitive, artistic, children’s language aspects with fun. The board game is expected to make children interact well so that all aspects of a child’s development run well. Keywords: Board games, Stimulation, Types of Children's Games